Kategorisasi Kejahatan Agresi Atas Tindakan Penggunaan Kekerasan Negara Perancis Pada Konflik Republik Mali Dalam Hukum Pidana Internasional - Zuhra, Nadia Maulida (Jurnal Selat, 2020)
International law has set any dispute resolution mechanisms between countries in the world that require peaceful means as the main approach. However, if a peaceful settlement of a dispute is not achieved, violence can also be used or acts of use of force against the country concerned, but it is limited to certain reasons with the legitimacy of the UN Security Council. The illustrated about the act of use of force is French on conflict of the Republic of Mali which caused 5 (five) civilians including children were death, so that these actions can be categorized as crimes of aggression. Therefore, the benchmarks for limitative acquisition of the use of force in question are crucial enough for the consideration of the state in taking intervention action. This study aims to examine the position of the use of force action of French against the Republic of Mali as crime of aggression and the legal consequences of an aggression offender country